Membranes of Polymer of Intrinsic Microporosity PIM-1 for Gas Separation: Modification Strategies and Meta-Analysis - Boya Qiu; Yong Gao; Patricia Gorgojo; Xiaolei Fan (Nano-Micro Letters)
Highlights Critical review of the polymers of intrinsic microporosity (PIM)-1-based membranes for applications in selective CO2 separation. State-of-the-art modification strategies for PIM-1 are thoroughly compared via meta-analysis. Key perspectives for progressing PIM-1 thin film membranes towards practical applications are suggested.